Inflammation induced by mast cell deficiency rather than the loss of interstitial cells of Cajal causes smooth muscle dysfunction in W/Wv mice - Winston, John H.; Chen, Jinghong; Shi, Xuan-Zheng; Sarna, Sushil K. (Frontiers in Physiology, 2014)
The initial hypothesis was that the interstitial cells of Cajal (ICC) acted as obligatory intermediaries of enteric neurotransmission to smooth muscle cells. Much information for this hypothesis came from studies in W/Wv mice lacking ICC. However, mast cells, which play critical roles in regulating inflammation in their microenvironment, are also absent in W/Wv mice. We tested the hypothesis that the depletion of mast cells in W/Wv mice generates inflammation in fundus muscularis externae (ME) that impairs smooth muscle reactivity to ACh, independent of the depletion of ICC. We performed experiments on the fundus muscularis externae from wild type (WT) and W/Wv mice before and after reconstitution of mast cells by bone marrow transplant. We found that mast cell deficiency in W/Wv mice significantly increased COX-2 and iNOS expression and decreased smooth muscle reactivity to ACh. Mast cell reconstitution or concurrent blockade of COX-2 and iNOS restored smooth muscle contractility without affecting the suppression of c-kit in W/Wv mice. The expression of nNOS and ChAT were suppressed in W/Wv mice; mast cell reconstitution did not restore them. We conclude that innate inflammation induced by mast cell deficiency in W/Wv mice impairs smooth muscle contractility independent of ICC deficiency. The impairment of smooth muscle contractility and the suppression of the enzymes regulating the synthesis of ACh and NO in W/Wv mice need to be considered in evaluating the role of ICC in regulating smooth muscle and enteric neuronal functions in W/Wv mice.